The Effectiveness of Prenatal Yoga on Back Pain in Third Trimester Pregnant Women at the Depok Clinic in 2022 - Chitra Ayuni Franisia; Febry Mutiariami Dahlan; Cholisah Suralaga (Institute of Computer Science (IOCS), 2022)
Pregnancy is a process that begins with the stage of conception until the birth of the fetus with a normal duration of 40 weeks or 280 days starting from the first day of the last menstruation. With increasing gestational age there are physical changes in the mother so that it can often cause complaints during pregnancy, one of which is back pain. It was found that low back pain in various regions of Indonesia reached 60-80% the incidence of back pain in pregnant women was still high. One of the efforts that can be done to overcome back pain during pregnancy is by doing prenatal yoga. To determine the effectiveness of prenatal yoga on back pain in third trimester pregnant women at the Depok Clinic in 2022. This type of research was a quasi-experimental design with pretest and posttest with control group design. The study was conducted at the Depok Clinic in 2022. The population in this study was 50 pregnant women TM III, the number of samples was 30 people. The sampling technique is purposive sampling. The data used is primary data. Data in univariate and bivariate analysis with Wilcoxon and Mann Whitney test. The data was processed using a computer with the SPSS program. The results of the univariate study showed that the average level of back pain in the control group at the first examination in third trimester pregnant women was 4.40 ± SD 0.828 and the second examination was 4.07 ± SD 0.799. The mean level of back pain in the intervention group before the intervention was 4.60 ± SD 0.828 and after the intervention was 2.07 ± SD 0.799.